Statistical analysis of the long-range transport of the 2015 Calbuco volcanic plume from ground-based and space-borne observations - (:unkn) unknown (My University, 2020)
This study investigates the influence of the 2015 Calbuco eruption (41.2 • S, 72.4 • W; Chile) on the total columnar aerosol optical properties over the Southern Hemisphere. The well-known technic of sun photometry was applied for the investigation of the transport and spatio-temporal evolution of the optical properties of the volcanic plume. The CIMEL sun photometer measurements performed at six South American and three African sites were statistically analysed. This study involves the use of the satellite observations and a back-trajectory model. The passage of the Calbuco plume is statistically detectable in the aerosol optical depth (AOD) observations obtained from sun pho-tometer and MODIS observations. This statistical detection confirms that the majority of the plume was transported over the northeastern parts of South America and reached the South African region 1 week after the eruption. The plume impacted the southern parts of South America to a lesser extent. The highest AOD anomalies were observed over the northeastern parts of South America. Over the South African sites, the AOD anomalies induced by the spread of the plume were quite homogeneously distributed between the east and west coasts. The optical characteristics of the plume near the source region were consistent with an ash-bearing plume. Conversely, sites further from the Calbuco volcano were influenced by ash-free plume. The optical properties discussed in this paper will be used as inputs for numerical models for further investigation of the ageing of the Calbuco plume in a forthcoming study.
Keywords: African Research